Analisis Minat Belajar dengan Menggunakan Media Pembelajaran Digital Sekolah Enuma - Yunita, Eka; Dhieni, Nurbiana; Nurjannah, Nurjannah (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
The use of appropriate digital learning media is crucial to attract children's interest in learning. Based on initial observations conducted at Puspita Kindergarten, researchers found that teachers have used digital learning media in learning. This study aims to analyze the learning interests of children aged 5-6 years using the digital learning media of Enuma School in Jati Pulo Village, Palmerah District and identify the role of Enuma School's digital learning media in fostering children's interest in learning. This study used a qualitative descriptive method involving 2 teachers and 3 children, data collection techniques in the form of observation, documentation, and descriptive analysis. The results showed that the use of Enuma School increased children's attention, active involvement, curiosity, and learning satisfaction. Enuma School's Digital Learning Media was proven to be able to attract children's interest in learning through interesting interactive and visual content. The contribution of this study provides insight to teachers and parents to provide appropriate learning media to attract children's interest in learning.